Effects of Rubber Seed Kernel Fermented with Yeast on Feed Utilization, Rumen Fermentation and Microbial Protein Synthesis in Dairy Heifers - Nirawan Gunun; Thanaporn Ouppamong; Pichad Khejornsart; Anusorn Cherdthong; Metha Wanapat; Sineenart Polyorach; Chatchai Kaewpila; Sungchhang Kang; Pongsatorn Gunun (Fermentation, 2022)
Yeast (Saccharomyces cerevisiae) has been used to improve the nutritive value of feedstuffs, especially rubber seed kernel. In the current study, rubber seed kernel was grated and subjected to solid-state fermentation with yeast to enhance the nutritive value. The yeast-fermented rubber seed kernel (YERSEK) was substituted for soybean meal in ruminant diets to evaluate the effect of YERSEK on feed intake, digestibility, rumen fermentation and microbial protein synthesis in dairy heifers. Five Holstein Friesian crossbred heifers with an initial body weight (BW) of 215 ± 20 kg were used in this research. The experimental design was a 5 × 5 Latin squared design and the dietary treatments were five levels of YERSEK at 0, 100, 150, 200 and 250 g/kg dry matter in concentrate at 1% of BW, with rice straw fed ad libitum. The supplementation with YERSEK reduced rice straw and total DM intake linearly (p < 0.05). The intake of neutral detergent fiber and acid detergent fiber decreased linearly (p < 0.05), while ether extract intake increased linearly (p < 0.01) with YERSEK supplementation. The ether extract digestibility tended to be high (p < 0.01) with increasing levels of YERSEK. Supplementation with the YERSEK did not change (p > 0.05) ruminal pH and blood urea nitrogen in this study, but ruminal ammonia nitrogen was increased (p < 0.01) in the heifers receiving YERSEK. Increasing the YERSEK levels did not adversely affect the proportion of volatile fatty acids (VFA), which included acetate, propionate and butyrate and the microbial population (p > 0.05). Microbial protein synthesis was similar among the treatments (p > 0.05). The inclusion of YERSEK at 250 g/kg DM in concentrate feed had no effect on the utilization of feed, rumen fermentation characteristics and microbial protein synthesis. The YERSEK could be used as a protein replacement for up to 86% of the soybean meal in feed concentrate for dairy heifers.